Which Factors do Older Adults Consider When Estimating the Time Left for Them to Live?. (24th April 2018) - Palgi, Yuval; Shrira, Amit; Kavé, Gitit; Rubinstein, Tom; Shmotkin, Dov
Abstract: Objectives: The present study examines which factors older adults consider as important when rating their subjective nearness-to-death (SNtD), as well as the associations between corresponding variables as reported in a multidimensional questionnaire and responses on a SNtD question. In addition, we examine whether importance ratings fit or diverge from the actual associations between corresponding variables and SNtD. Method: Two hundred and seventy-two participants (average age 80.75) reported their health and functioning, their SNtD, and the importance of each of 13 preselected factors in evaluating SNtD. Results: Respondents considered physical functioning and psychological factors as the most important factors to their SNtD evaluation, and genetic factors (i.e., age, gender, parental longevity) as the least important. Ratings of importance were strongly and positively correlated with the strength of the associations between the corresponding variables and SNtD. Discussion: Older adults appear to have implicit knowledge of the factors that affect their SNtD. Yet, this knowledge is sometimes biased and does not necessarily represent variables that have been identified as related to actual longevity.